AI-POWERED CONTRACT RISK SCORING: THE DEVELOPMENT OF A CONTRACT RISK SCORING ENGINE - Niraj Ittan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article describes the creation and deployment of an artificial intelligence Contract Risk Scoring Engine, a transformative solution that has generated revenue through its innovative approach to contract analysis. The system automatically identifies and evaluates high-risk clauses and terms in both legacy and current contracts using advanced machine learning techniques and natural language processing. The solution significantly improves analysis accuracy compared to traditional manual review processes through the implementation of custom AI models specifically trained on contract language. The system is positioned as a cornerstone of modern contract intelligence through its sophisticated risk assessment framework, weighted scoring algorithms, and seamless integration capabilities. This article explores the technical architecture, model training methodology, and practical implementation challenges while also examining the broader business impact and market implications of introducing AI-driven risk assessment to contract management. The success of this initiative not only demonstrates the practical application of AI in legal technology but also provides valuable insights into the development of enterprise-scale machine learning solutions that drive significant business value.